Emotional Literacy in Vulnerable Contexts with Digital Drawings - Holguin-Alvarez, Jhon; Cruz-Montero, Juana; Apaza-Quispe, Juan; Merino Flores, Irene; Ruiz-Salazar, Jenny (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective sought to determine the effects on emotional literacy in the elaboration of digital drawings and traditional drawings in the cooperative and individual pedagogical format. 120 schoolchildren from vulnerable contexts participated. The data was collected by a scale based on Fury's proposals. Se advierten efectos de mejora en el cambio de la alfabetización emocional, y en sus componentes de expresividad y valencia. Improvement effects are noted in the change of emotional literacy, and in its components of expressiveness and valence. A higher level was detected in the change from negative to positive emotions in the drawings of children who used tablets collaboratively, as opposed to those who did so individually